Corn (Zea mays L) Development Based on Drone-Based Vegetation Index Trough NPK Fertilization - Padjung, Rusnadi; BDR, Muh. Farid; Adzima, Ahmad Fauzan; Saleh, Ifayanti Ridwan; Musa, Yunus; Nasaruddin, N.; Anshori, Muhammad Fuad; Muharram, Nur Qalbi Zaesar; Amier, Nirwansyah (Agrotech Journal, 2023)
Maize is one of the most important food crops after rice. This study aimed to obtain one or more doses of fertilizers that provide high growth and productivity, obtain one or more varieties of maize that have increased productivity, and obtain interactions between doses of fertilizers with maize varieties that deliver high growth and productivity. The research was conducted at the Experimental Farm (KP) of the Bajeng Cereal Crops Research Center, Bajeng District, Gowa Regency, South Sulawesi. At an altitude of 27.2 meters above sea level, with coordinates 5018'21.5 "N, 119028'38.6 "E and an average temperature of 28.50C. The research wasÂ conducted from September to December 2022. This study used a separate plot design, fertilizer dose as the main plot consisting of 3 fertilizer doses, namely N:P:K equals 160:120:80 kg N.ha-1, N:P:K equals 200:150:100 kg N.ha-1, and N:P:K equals 240:180:120 kg N.ha-1. The subplots were corn varieties: Sinhas 1, Jakarin, Nasa 29, JH 36, Bisi 18, ADV Joss and Pioner. The fertilizer dose with the highest productivity compared to the other five is N:P:K equals 240:180:120, with an average productivity of 6.66 t.ha-1. The variety that produces the highest productivity compared to the two types is ADV Joss, with an average productivity of 9.28 t.ha-1. The combination of N:P:K fertilization dose equals 160:120:80 with ADV Joss variety gave the highest productivity compared to the combination of fertilization dose and other types with an average productivity of 9.38 t.ha-1. The correlation between productivity and parameters such as plant height, number of leaves, cob weight, cob diameter, cob length, cob length, number of seed rows per cob, seed yield, 1000 seed weight, and NDVI showed a positive interaction.Â